Initial Assessment of Tidal Current Energy Resource at Aroih Raya, at Aceh Waters, Indonesia using Delft3D Numerical Modelling - Pratama, Munawir; Chosyi, Miftahul; Jamila, Farda; Liana, Revi Rosa (Institut Teknologi Bandung, 2025)
Abstract Tidal energy is one of the renewable energy sources that could be utilised to reduce Indonesia's carbon emissions produced in the energy sector. Many straits have been studied for tidal current energy; however, several straits in Western Indonesia Waters have yet to be studied. In this study, a depth-averaged tidal flow numerical modelling is conducted, with the aim of assessing the tidal current energy resources at Aroih Raya, at Aceh Waters, Northwestern tip of Sumatra Island. The modelling employed the Delft3D-FLOW suite, prescribed with GEBCO bathymetry and TPXO boundary conditions. The model achieved a good validation against a tidal elevation measurement and produced a qualitative similarity to the flow pattern recorded in a navigational book. The modelling output revealed the most energetic flow is situated at the bottleneck of the strait going westward and eastward, with flow speed reaching 2 m/s during spring tide conditions. With five cells identified as potential sites, the Sabelle D10 turbine was found to be suitable for the water depth and current velocity characteristics. Preliminary projection revealed that with 25 turbines at each cell, the projected technical resource is 4,993 MWh for a three-month period. Overall, this tidal current can accommodate 2.58% of Aceh Besar's electricity needs by 2044. Keywords : Aroih raya, Delft3D, hydrodynamic modelling, marine renewable energy, tidal current. Abstrak Energi pasang surut merupakan salah satu sumber energi terbarukan yang dapat digunakan untuk mengurangi emisi karbon dari sektor energi di Indonesia. Banyak selat yang telah diteliti untuk energi arus pasang surut, namun beberapa selat di Perairan Indonesia bagian Barat belum pernah diteliti. Dalam penelitian ini dilakukan pemodelan numerik rata-rata kedalaman arus pasang surut yang bertujuan untuk menilai sumber daya energi arus pasang surut di Aroih Raya, Perairan Aceh, Pulau Sumatera. Pemodelan ini menggunakan perangkat lunak Delft3D-FLOW, yang ditentukan dengan batimetri GEBCO dan kondisi batas TPXO. Model mencapai validasi yang baik terhadap pengukuran elevasi pasang surut dan menghasilkan kemiripan kualitatif dengan deskripsi arus dalam buku navigasi. Hasil pemodelan menunjukkan bahwa aliran yang paling energik terletak di bagian bottleneck selat yang mengarah ke barat dan timur, dengan kecepatan aliran mencapai 2 m/detik pada kondisi pasang surut. Terdapat lima sel yang diidentifikasi sebagai lokasi potensial, turbin Sabelle D10 dipilih karena sesuai dengan kedalaman air dan karakteristik kecepatan arus. Proyeksi awal menunjukkan bahwa dengan 25 turbin di setiap sel, sumber daya teknis yang diproyeksikan adalah 4.993 MWh untuk periode tiga bulan. Secara keseluruhan, arus pasang surut ini mampu mengakomodasi 2,58% kebutuhan listrik di Aceh Besar pada tahun 2044. Kata Kunci : Aroih raya, arus pasang surut, Delft3D, energi terbarukan laut, pemodelan hidrodinamika.